ANTECEDENTS, AND DEVELOPMENT OF THE SACRED CHORAL CONCERTO IN RUSSIA - VÉGH, Mónika (Studia Universitatis Babes-Bolyai Musica, 2020)
Upon dealing with Russian religious choral music of the 18th century, one may clearly recognize the outlines of a unique genre, the duhovny kontsert, or in other words, the genre of the religious choral concerto. The subject is suppletory, since very few people in Hungary have dealt with pre-19th century Russian music, let alone with choral repertoire. In the present study, we may follow up the legalization and development of polyphony in church music – which was strictly monophonic up until the 1500s – and the different types of multivocal hymns. We will also get to know the Russian composers of the 17th and 18th centuries, who contributed to the genre with their own works. We will receive a detailed description about concertante techniques used in European vocal music, and about their appearance in the 18th century Russia, which was unique to a cappella choral concerto. We will also get to know more about the structure and characteristics of the duhovny kontsert, while taking a glance at the historical background. In the final part of the study, we will see how the genre influenced subsequent eras, and how the stylistic marks and techniques appear in the choral oeuvre of Rachmaninoff.